Efektivitas Penggunaan Aplikasi Belajar Bahasa Inggris Dalam Meningkatkan Kemampuan Speaking dan Listening Sebagai Mahasiswa Sastra Inggris - Ayuna Junaida, Alfian (Maliki Interdisciplinary Journal, 2025)
It is a requisite for students of English Literature to develop proficiency in both speaking and listening skills in order to master the English language. In light of the technological advancements that have occurred in recent times, it is evident that a multitude of foreign language learning applications have emerged as a viable alternative for students. Such applications provide users with the ability to access foreign language learning materials at any time and from any location. It is essential that English Literature students develop proficiency in speaking skills, which are crucial for effective communication with lecturers and classmates during academic activities. English Literature students must develop their listening skills, which entail hearing and understanding the vocabulary spoken by the speaker. It is essential to balance listening skills with speaking skills, as if these two skills are not mastered, students will encounter difficulties in communicating if they do not have the same understanding. Consequently, the effectiveness of using English learning applications in improving speaking and listening skills is beneficial and effective for students who wish to enhance their mastery of these skills.